Primary care practice-based care management for chronically ill patients (PraCMan): study protocol for a cluster randomized controlled trial (ISRCTN56104508) - Freund, Tobias; Peters-Klimm, Frank; Mahler, Cornelia; Baldauf, Annika; Szecsenyi, Joachim (Trials, 2011)
Care management programmes are an effective approach to care for high risk patients with complex care needs resulting from multiple co-occurring medical and non-medical conditions. These patients are likely to be hospitalized for a potentially "avoidable" cause. Nurse-led care management programmes for high risk elderly patients showed promising results. Care management programmes based on health care assistants (HCAs) targeting adult patients with a high risk of hospitalisation may be an innovative approach to deliver cost-efficient intensified care to patients most in need.
Gesehen am: 19.04.2023